The Influence Of Implementation Relationship Marketing Toward Customer Loyalty Nissan Mlati Yogyakarta - Muhammad Fikry Januar; Rosena Shintabella; Zulfikar Fauzi (Journal of Applied Digital Business Management, 2024)
The research was to determine the effect of trust, commitment, and communication as a key factor of relationship marketing either partially or simultaneously on customer loyalty Nissan Mlati Yogyakarta. In this study used non-probability sampling method with a sampling technique using purposive sampling and obtained a valid sample of 70. To find out how much the dependent variable changes in the independent variables used multiple linear regression analysis. Test instrument used in this study is to test the validity and reliability testing. As for the hypothesis test used the F test and t test. From the results of the hypothesis the variable trust, commitment, and communication significantly affect simultaneously on customer loyalty. Commitment and communication partially significant effect on customer loyalty while partial trust no significant effect on customer loyalty This suggests that customer loyalty will increase if the Nissan Mlati Yogyakarta improve relationship marketing variables, that include trust, commitment, and communication.